From learner to teacher: (re)training graduate teaching assistants' teaching approaches and developing self-efficacy for and interest in teaching. Issue 7 (10th November 2021) - Shum, Alex; Lau, Peter; Fryer, Luke
ABSTRACT: Graduate students often teach in higher education but lack necessary experience, while enrolment for teacher-training courses is often voluntary with varying standards. The development and malleability of graduate students' teaching approaches, self-efficacy, interest and teaching ability were evaluated in a mandatory teaching course at a research-intensive university using latent SEM (variable-centred) and latent profile transition (person-centred) analyses. Participants ( n  = 310) completed items from the Approaches to Teaching Inventory, Teacher's Sense of Efficacy Scale, and Teaching Interest Scale at the beginning and end of the course. Trainers assessed participants in end-of-course teaching. Prior student-focused teaching predicted future self-efficacy ( β  = .30) which predicted achievement (end-of-course teaching, β   =  .33). Prior self-efficacy was also found to predict future interest ( β  = .17). Initial differences in teaching approach reported by STEM and non-STEM participants did not persist, suggesting training can shape and alter previous conceptions. Three subgroups: Low-Teacher-Focused, Mid-Mixed, and High-Student-Focused indicated a developmental progression in teaching beliefs. Results suggest teaching beliefs can be developed and shaped during a short course. Theoretical and practical implications are discussed.